Needs Assessment on Research Capability of Secondary School Teachers: Basis for an Extension Program - Nanette D. Bilbao; Ronette Chris D. Bilbao; Rhea T. Mandaya; Jannice M. Asaraji (PT ARRUS Intelektual Indonesia, 2024)
This study assessed the demands on secondary school teachers' research abilities and served as the basis for an extension program of secondary teachers in Dumingag, Zamboanga del Sur for academic year 2021–2022. Focus Group Discussions (FGD) and questionnaire-checklist were used in the descriptive survey method. The findings show that more teacher participants need extra training in research education due to their low levels of research literacy. The reading and writing levels of the teacher participants were, however, assessed differently by school administrators and teachers, as seen by the grand averages of 2.49 and 2.84. Additionally, the teacher participants faced the following major problems: a lack of time for conducting research, a lack of writing research skills, difficulty in organizing one's thoughts, a lack of reading materials as references, a lack of knowledge for statistical data treatment, and a lack of funds to hire a statistician for statistical data. Based on the results, the following needs and services were also determined by the participants: research methods and design; essential research writing skills; how to format a research paper; and where to get resources. The needs assessments of the teacher participants with regard to research competence also showed a sizable discrepancy.